El análisis financiero y evaluación de los indicadores de la gestión, endeudamiento y liquidez y la toma de decisiones - Tituana Armijos, Patricia Katherine (2015)
This research project can meet the objectives and refer to an analysis and interpretation of financial statements applying indicators in order to know the real economic and financial situation of the Association of Small Producers BANANA, City Passage in 2013 and 2014 periods, and leave the respective report with recommendations that will help improve the financial management of the company. The methodology for the development of this work was the quantitative approach, descriptive level, non-experimental design. Using the technique also bibliográfica- documentary to analyze criteria conceptualizations and authors as a theoretical basis for this research, technical field, making interview the manager and accountant, and the observation of accounting business processes in order to gather Company information needed to apply the procedures of financial analysis, therefore, the aim of this integration project is to apply basic financial ratios to assess the management carried out by the administration. After applying the analysis and interpretation of financial statements, marketing bananas and agrochemicals was concluded that the association. Insufficient liquidity to meet its current obligations and maintain a reasonable working capital is observed, that because the average collection period is greater than the payment to their suppliers, focusing on the debt of the company with third parties. I suggest to the Association analyze their financial statements annually with the purpose of verifying negative issues for the Association and make decisions to guide improve profitability.